A comprehensive urban programme to reduce energy poverty and its effects on health and wellbeing of citizens in six European countries: study protocol of a controlled trial - Merel Stevens; Hein Raat; Maite Ferrando; Beatriz Vallina; Rebeca Lucas; Lucie Middlemiss; Josep Rédon; Elena Rocher; Amy van Grieken (BMC, 2022)
Abstract Background Nearly 11% of the European population is affected by energy poverty. Energy poverty is defined by the European Commission (2016) as the inability to afford basic energy services to guarantee a decent standard of living. Energy poverty is considered a complex, multidimensional problem that affects environment, housing, urban development, and health. Living in energy poverty conditions is associated with poorer human health and wellbeing. Hence, the WELLBASED intervention programme aims to design, implement and evaluate a comprehensive urban programme, based on the social-ecological model, to reduce energy poverty and its effects on the citizens' health and wellbeing in six European urban study sites: Valencia, Spain; Heerlen, The Netherlands; Leeds, United Kingdom; Edirne, Turkey; Obuda, Hungary, and; Jelgava, Latvia. Methods A controlled trial is performed. A total of 875 participants are recruited (125-177 per study site) to receive the WELLBASED intervention programme for 12 months (intervention condition) and 875 participants act as controls (control condition). Data will be collected with a baseline measurement at inclusion (T0), and follow-up measurements after 6 months (T1), 12 months (T2), and 18 months (T3). In both study arms, effects of the WELLBASED intervention programme are measured: health-related quality of life (HR-QoL), mental health, frailty in older adults, self-perceived health, chronic conditions, and care utilization. At the same time points, household expenditure on energy and energy consumption are obtained. In the intervention arm, health-monitoring data (i.e. peak flow, oxygen saturation, blood pressure, and heart rate) are obtained monthly and sleep quality with a three-month interval. Household data with regard to temperature, humidity and air quality are collected near real-time by home sensors. Qualitative interviews are conducted in each study site to evaluate the impacts of the WELLBASED intervention programme and to help explain findings. Discussion The WELLBASED intervention programme will provide new insights into the effectiveness of a comprehensive urban programme to tackle energy poverty and its effects on health and wellbeing across Europe. Hence, this study can contribute to European-wide replicable solutions for policy-makers and city practitioners to alleviate energy poverty. Trial registration ISRCTN registry number is ISRCTN14905838 . Date of registration is 15/02/2022.